Intestinal parasitosis in asylum seekers from the Middle East and South Asia - Relić, Tijana; Kačarević, Hranislav; Ilić, Nevenka; Jovanović, Dara; Tambur, Zoran; Doder, Radoje; Lazarević, Ivana (Vojnosanitetski pregled, 2021)
Background/Aim. It is estimated that about 230 million refugees and asylum seekers circulates worldwide. Parasitosis are diagnosed in recent years with increasing frequency both in Europe and other developed countries. International migration of population, as an inalienable part and a result of the process of globalization, has an increasing impact on health of the population of countries through which migrants pass or settle. The aim of this study was to determine the incidence of intestinal parasitic diseases in asylum seekers on the territory of Belgrade. Methods. The study group included 97 asylum seekers from the Centre for Asylum seekers in Obrenovac, in the period December 2013–January 2014. Stool samples were taken less than seven days after arriving to the Center and sent to the Laboratory for Parasitological Diagnosis of the Public Health Institute of Belgrade. Detection of parasites in stool samples was performed by a direct native slide made of fresh sample and direct slide made after stool concentration applying "Mini Parasep" technique. Statistical analysis included application of χ2-test of matching and χ2-test of independence. Results. The study showed that the parasites were detected in 9.3% of cases, in the group of 15–24 years of age. Protozoa were found in 6.2% and helminthes in 3.1% of the samples. Conclusion. Most intestinal parasitosis were found in asylum seekers from Bangladesh. All parasitosis were found in males and the most frequently detected parasite was Giardia lamblia.